2017
DOI: 10.1016/j.bbi.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Protection against alcohol-induced neuronal and cognitive damage by the PPARγ receptor agonist pioglitazone

Abstract: Binge alcohol drinking has emerged as a typical phenomenon in young people. This pattern of drinking, repeatedly leading to extremely high blood and brain alcohol levels and intoxication is associated with severe risks of neurodegeneration and cognitive damage. Mechanisms involved in excitotoxicity and neuroinflammation are pivotal elements in alcohol-induced neurotoxicity. Evidence has demonstrated that PPARγ receptor activation shows anti-inflammatory and neuroprotective properties. Here we examine whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 69 publications
(102 reference statements)
0
28
0
1
Order By: Relevance
“…Neuroanatomical evidence of PPAR␥ expression in AMY, HIPP, and other brain regions involved in the regulation of emotion and motivation have been previously described (Moreno et al, 2004;Inestrosa et al, 2005;Gofflot et al, 2007;de Guglielmo et al, 2015). Cortical and amygdalar PPAR␥ activation has been linked to the attenuation of the negative effects induced by acute and chronic stress exposure (García-Bueno et al, 2005;Domi et al, 2016) and specific hippocampal PPAR␥ activation appears to play a role in attenuating the cognitive deficits caused by alcohol intoxication (Cippitelli et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Neuroanatomical evidence of PPAR␥ expression in AMY, HIPP, and other brain regions involved in the regulation of emotion and motivation have been previously described (Moreno et al, 2004;Inestrosa et al, 2005;Gofflot et al, 2007;de Guglielmo et al, 2015). Cortical and amygdalar PPAR␥ activation has been linked to the attenuation of the negative effects induced by acute and chronic stress exposure (García-Bueno et al, 2005;Domi et al, 2016) and specific hippocampal PPAR␥ activation appears to play a role in attenuating the cognitive deficits caused by alcohol intoxication (Cippitelli et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…In our study, drinking status with CHD5 rs11121295 variant presented a promising association with Alzheimer's disease risk compared with non-drinking carrying that genotype, which indicated that this variant might act in response to drinking, and true associations might be detected by alcoholic stimulation. It has been shown that alcohol could modulate the effect of various cytokines, receptors or neuroimmune signaling in brain, such as midkine (MDK) [ 24 ], PPARgamma receptor [ 25 ], and HMGB1, miRNA and TLR receptors [ 26 ]. Therefore, we speculated, alcohol intake might trigger proinflammatory events through their induction of oxidative stress and extensive inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It has three subtypes: PPARα, PPARβ (δ) and PPARγ. Antidiabetic effects of TZDs have been found to be closely related to the ability to bind to and activate the PPARγ [4] . TZDs have effects on the vascular.system.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular effects occur via the activation of peroxisome proliferator-activated receptors (PPARs) [3] . Activation of PPARγ is known to regulate inflammatory responses.and reduce the expression of many proinflammatory genes (COX-2, iNOS and cytokines), and it is also associated with inflammation in neurodegeneration [4] . Pioglitazone (PGT), a member of this group, is thought to have neuronprotective property through several mechanisms by increasing the gene transcription with the agonistic effect of PPARγ.…”
Section: Introductionmentioning
confidence: 99%